A Volume of Fluid (VoF) based all-mach HLLC Solver for Multi-Phase Compressible Flow with Surface-Tension - Oomar, Muhammad Yusufali (Department of Mechanical Engineering, 2021)
This work presents an all-Mach method for two-phase inviscid flow in the presence of surface tension. A modified version of the Hartens, Lax, Leer and Contact (HLLC) approximate Riemann solver based on Garrick et al. [1] is developed and combined with the popular Volume of Fluid (VoF) method: Compressive Interface Capturing Scheme for Arbitrary Meshes (CICSAM). This novel combination yields a scheme with both HLLC shock capturing as well as accurate liquid-gas interface tracking characteristics. To ensure compatibility with VoF, the Monotone Upstream-centred Scheme for Conservation Laws (MUSCL) [2] is applied to non-conservative (primitive) variables, which yields both robustness and accuracy. Liquid-gas interface curvature is computed via both height functions [3, 4] and the convolution method [5]. This is in the interest of applicability to both cartesian and arbitrary meshes. The author emphasizes the use of VoF in the interest of surface tension modelling accuracy. The method is validated using a range of test-cases available in literature. The results show flow features that are in agreement with experimental and benchmark data. In particular, the use of the HLLC-VoF combination leads to a sharp volume fraction and energy field with improved accuracy (up to secondorder).